2009
DOI: 10.2172/983681
|View full text |Cite
|
Sign up to set email alerts
|

Effect of composition on the density of multi-component molten nitrate salts.

Abstract: The density of molten nitrate salts was measured to determine the effects of the constituents on the density of multi-component mixtures. The molten salts consisted of various proportions of the nitrates of potassium, sodium, lithium and calcium. Density measurements were performed using an Archimedean method and the results were compared to data reported in the literature for the individual constituent salts or simple combinations, such as the binary Solar Salt mixture of NaNO3 and KNO3. The addition of calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…The buoyant force can then be calculated by measuring the difference in the mass of the bob at two states: immersed in the molten salt and in air at ambient temperature. This mass difference is then divided by the volume of the bob, as shown in below, to determine the density of the molten salt [30].…”
Section: Molten Salt Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…The buoyant force can then be calculated by measuring the difference in the mass of the bob at two states: immersed in the molten salt and in air at ambient temperature. This mass difference is then divided by the volume of the bob, as shown in below, to determine the density of the molten salt [30].…”
Section: Molten Salt Densitymentioning
confidence: 99%
“…Surface tension effects on the wire were determined to be negligible due to the very small diameter of the wire (0.02 mm). Bradshaw [30] showed that surface tension forces on the wire were negligible for a wire for a 0.2 mm diameter wire and a bob of similar weight. The focus of this research is to measure the density of LiCl-KCl salt as a function of lanthanide chloride concentration.…”
Section: Molten Salt Densitymentioning
confidence: 99%
“…As would be expected, the heavier alkali and alka line earth metal nitrates are more dense than their lighter salts of the same group (CsNO 3 ; d = 2.82 g/mL vs. LiNO 3 ; d = 1.69 g/mL) [25]. The density of binary and ternary mix tures of nitrate and nitrite salts also behaves linearly with temperature [26][27][28]. The density of mixtures can be ap proximated with high accuracy based on the mole percent of each individual constituent.…”
Section: Thermophysical Propertiesmentioning
confidence: 69%
“…At elevated temperatures (above 300 °C) the viscosity decreases to below 5 cP or less [26,27]. Mixtures contain ing calcium are slightly more viscous compared to all alkali metal mixtures.…”
Section: Thermophysical Propertiesmentioning
confidence: 98%
“…However, published work on the mixing behaviour of molten salts is limited. Work at Oak Ridge National Laboratory (ORNL) and Sandia National Laboratories found that the density of a molten salt mixture could be predicted by weighing the molar volumes of each of the salt constituents of the mixture by their molar fraction and summing [3,9,10,11]. This simple linear addition is also known as ideal mixture behaviour, Vegard's law and…”
mentioning
confidence: 99%